The Impact of Green Tea Consumption on Cardiovascular Disease - Muntaha Noor, Muhammad Musa Khan, Fatima Tuz Zahra, Ishaa Basharat, Muhammad Safdar Luqman, Umar Tanveer (Pakistan Journal of Medical & Health Sciences, 2024)
Aims: Cardiovascular diseases (CVDs) remain one of the leading causes of morbidity and mortality worldwide. Recent studies have highlighted the potential benefits of dietary interventions, particularly green tea, in the prevention and management of CVDs. This systematic review aims to evaluate the existing literature on the impact of green tea consumption on cardiovascular disease outcomes. Methodology: A systematic review was conducted, including a total of 20 studies that examined the relationship between green tea intake and various cardiovascular risk factors. The bioactive compounds in green tea, such as catechins and flavonoids, were analyzed for their antioxidant, anti-inflammatory, and lipid-lowering effects. Results: The findings suggest that regular green tea consumption may contribute to improved blood lipid profiles, reduced blood pressure, and enhanced endothelial function, all of which are critical for reducing cardiovascular risk. Conclusion: Green tea shows promising potential in mitigating cardiovascular risk factors. However, further high-quality randomized controlled trials (RCTs) are needed to confirm these benefits and establish optimal dosages for effective prevention and management of CVDs. Keywords: Green tea, Cardiovascular disease, Antioxidants, Blood pressure, Lipid profile.